2016
DOI: 10.1016/j.tetlet.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

A mild and efficient approach to enantioenriched α-hydroxyethyl α,β-unsaturated δ-lactams

Abstract: A straightforward approach toward enantioenriched α-substituted α,β-unsaturated δ-lactams is described. Although a considerable number of approches toward α,β-unsaturated δ-lactams have been reported, there are relatively few examples of enantioenriched α,δ-disubstituted α,β-unsaturated δ-lactams formation. The δ-stereocenter was formed by addition of allylmagnesium bromide to an N-tert-butylsulfinyl imine. The α,β-unsaturated δ-lactam was furnished by ring-closing metathesis. Although Baylis-Hillman chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In the course of a synthesis of lactam derivatives, the allylation of sulfinimides was used to prepare starting materials with high optical purity (Scheme ). Other authors had performed the same reaction with the enantiomeric starting material and reported the opposite stereochemical outcome (Scheme ). It is likely that the structure of 1063 had been misassigned …”
Section: Additions Of Allylmagnesium Reagents To Imines and Related S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the course of a synthesis of lactam derivatives, the allylation of sulfinimides was used to prepare starting materials with high optical purity (Scheme ). Other authors had performed the same reaction with the enantiomeric starting material and reported the opposite stereochemical outcome (Scheme ). It is likely that the structure of 1063 had been misassigned …”
Section: Additions Of Allylmagnesium Reagents To Imines and Related S...mentioning
confidence: 99%
“… Other authors had performed the same reaction with the enantiomeric starting material and reported the opposite stereochemical outcome (Scheme ). It is likely that the structure of 1063 had been misassigned …”
Section: Additions Of Allylmagnesium Reagents To Imines and Related S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1: Yields for the Grignard reaction of lactam 6 giving products 7 and 8. Lactam 4 may also be selenylated and eliminated to give the unsaturated derivative 9; 33 since such a,b-unsaturated lactams 42 are quite electrophilic and suitable for a variety of nucleophilic addition processes, 43,44 and our earlier work had demonstrated efficient epoxidation of these systems, 33 an obvious question was its applicability to dihydroxylation processes, which in any case would provide a closer set of mimics to pramanicin 1. However, although an earlier examination of a closely related ester had indicated successful dihydroxylation using osmium tetroxide or potassium permanganate was possible but that product isolation was problematic, application of the ruthenium-mediated "flash dihydroxylation" procedure reported by Shing and co-workers 45 to 9…”
Section: Resultsmentioning
confidence: 99%
“…Bromides 9 and 10 can be prepared by bromination of the double bond in 11 and 12 and the subsequent elimination of HBr, while 11 and 12 can be easily synthesized from 13 and 14 through the RCM reaction. Since Grubbs’s group reported the synthesis of conformationally restricted amino acids and peptides using olefin metathesis, this method has been employed by several groups for the synthesis of dipeptide mimetics with azabicyclic core structures. ,, …”
mentioning
confidence: 99%